Interfacial microstructure and local bonding strength of magnetic pulse welding joint between commercially pure aluminum 1060 and AISI 304 stainless steel. (October 2019) - Lu, Zhenyang; Gong, Wentao; Chen, Shujun; Yuan, Tao; Kan, Chunlei; Jiang, Xiaoqing
Abstract: A commercially pure aluminum 1060 tube flyer and an AISI 304 stainless steel bar were joined using various magnetic pulse welding parameters (discharge voltage, radial gap, overlap length). The results revealed that the local bonding strength distribution along the axial direction of the joint is a U-shape curve. Moreover, the joint could be divided into three zones (Zones I, II, and III) along this direction. The middle part of the joint (Zone II) was actually a non-effective bonding zone, whereas Zones I and III were effective bonding zones. Furthermore, when the overlap length was reduced, the impacting mode of the magnetic pulse welding changed from 'double-orientation' to 'single-orientation', and the non-effective bonding zone could be prevented by reducing the overlap length to 6 mm. In addition, the overall bonding strength of the joint increased with increasing discharge voltage, but decreased with increasing radial gap.